2018
DOI: 10.1051/e3sconf/20185301015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis And Study On Distribution Of Defect Electric Field On Basin-type Insulator In GIS

Abstract: With the increase of electric network voltage in power system, the internal discharge phenomenon of gas insulated substation (GIS) during operation often happens. In this paper, a 3-D simulation model of GIS with metal protrusion on basin-type insulator was utilized to study the effect of metal protrusion on the electric field distortion in GIS. It can be concluded from simulation results that the electric field increases with the height of metal protrusion when the radius is constant, while decrease with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Wensheng Gao et al [29] have been identified that partial discharge occurs due to four types of typical defects like floating metal, depression, particle on the spacer, and void in solid insulation and analyzed their effects at different sizes of each defect for observing the consistency frequency spectrum characteristics. Qikun Feng et al [30] has studied the effect of metal depression on concave sides of the basin-type insulator in GIS at different heights and radii of metal depression and observed that at high voltage conductor the electric field stress is higher than that of grounded enclosure. Feng-Chang Gu et al [31] has identified four GIS models with typical defects where the models include internal conductor of porcelain bushing at load side like Type 1: Conductor of porcelain bushing containing oil grease, Type 2: Gas tank containing metal particles, Type 3: Operation handle containing welding depression, Type 4: Metal ring with an abrasion defect.…”
Section: Introductionmentioning
confidence: 99%
“…Wensheng Gao et al [29] have been identified that partial discharge occurs due to four types of typical defects like floating metal, depression, particle on the spacer, and void in solid insulation and analyzed their effects at different sizes of each defect for observing the consistency frequency spectrum characteristics. Qikun Feng et al [30] has studied the effect of metal depression on concave sides of the basin-type insulator in GIS at different heights and radii of metal depression and observed that at high voltage conductor the electric field stress is higher than that of grounded enclosure. Feng-Chang Gu et al [31] has identified four GIS models with typical defects where the models include internal conductor of porcelain bushing at load side like Type 1: Conductor of porcelain bushing containing oil grease, Type 2: Gas tank containing metal particles, Type 3: Operation handle containing welding depression, Type 4: Metal ring with an abrasion defect.…”
Section: Introductionmentioning
confidence: 99%